Pengaruh Total Quality Management (TQM) Terhadap Kinerja Umkm Yang Dimedasi Komitmen Organisasional Studi Pada Umkm Kota Ternate - Nindah Ayu Lestari; Abdullah W. Jabid; Adnan Rajak (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to examine and analyze the effect of Total Quality Management (TQM) on MSME Performance Mediated by Organizational Commitment Study on MSMEs in Ternate City. The approach used in this research is a quantitative approach. This type of research uses quantitative and causal. The population in this study were UMKM actors located in the Ternate City area. The UMKM population spread across Ternate City according to a page accessed from the Ministry of UMKM Cooperatives as many as 20,164 UMKM and by using the Slovin formula, a sample of 100 UMKM actors was obtained. The data analysis method uses SmartPLS software version 3.0. The results show that 1) total quality management has a significant effect on UMKM performance, 2) total quality management has a significant effect on organizational commitment, 3) organizational commitment has a significant effect on UMKM performance, 4) organizational commitment is able to mediate the relationship between the effect of total quality management on the performance of UMKM.